Study on 46 XY Disorders of Sex Development (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: 46 XY disorders of sexual development (DSD) include a wide sphere of phenotypes which can be ambiguous male genitalia with or without hypospadias, unambiguous female genitalia or dysgenetic gonads or any combination of them. Management of these patients depends on the aetiology, age at presentation, gender orientation and advancement in feminization.Objectives: To assess the clinical, biochemical, radiological and chromosomal profile of the paediatric patients with suspected DSD attending a tertiary level healthcare centre and plan for appropriate management.Materials and Methods: This cross-sectional study was carried out among 30 cases of 46XY DSD attending the paediatric endocrine unit of Bangladesh Institute of Research and Rehabilitation in Diabetes Endocrine and Metabolic Disorders (BIRDEM) General Hospital from May 2016 to April 2017. Clinical, biochemical, radiological and chromosomal evaluations were done to identify the cause of DSD.Results: The mean age of the patients recruited in the study was 3.51 (±5.03) years ranging from 13 days old to 13 years old. Among these 30 patients, the chief complaint was ambiguous genitalia in 29 (96.7%) cases, 1 (3.3%) case with Micropenis and 1 (3.3%) case with absence of development of secondary sexual characteristics. The gender of rearing was male in 23 (76.7%) cases and rest as female. Among the patients 5 (16.67%) patients were diagnosed with PAIS, 5 (16.67%) patients with CAIS, 3 (10%) patients had a deficiency of 5αRD and gonadal dysgenesis was found in 5 (16.67%) patients. The corrective surgery was done in 5(16.67%) patients, 16 (53.3%) patients referred to surgeon for operative treatment and 7(23.3%) patients were prescribed to administer testosterone.Conclusions: The early presentation, correct identification of the cause and initiation of cause-based treatment can abate the physical and psychosocial complications and may support better gender orientation related adjustability.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 134-138